From Orientalism to Cultural Capital The Myth of Russia in British Literature of the 1920s - Soboleva, Olga (Peter Lang International Academic Publishers, 2017)
From Orientalism to Cultural Capital presents a fascinating account of the wave of Russophilia that pervaded British literary culture in the early twentieth century. The authors bring a new approach to the study of this period, exploring the literary phenomenon through two theoretical models from the social sciences: Orientalism and the notion of «cultural capital» associated with Pierre Bourdieu. Examining the responses of leading literary practitioners who had a significant impact on the institutional transmission of Russian culture, they reassess the mechanics of cultural dialogism, mediation and exchange, casting new light on British perceptions of modernism as a transcultural artistic movement and the ways in which the literary interaction with the myth of Russia shaped and intensified these cultural views.